FILSAFAT PENDIDIKAN SEBAGAI PONDASI DASAR LEMBAGA PENDIDIKAN ISLAM - Syaiful; Ma'mur, Ilzamudin; Gunawan, Agus; Syam, Ahmad Bazari (Qolamuna : Jurnal Studi Islam, 2023)
Educational philosophy is an integral part of the principal or foundation that aims to promote education quality. Islamic education is the focus for most Muslims, so it is necessary to develop the values or philosophical principles of Islamic education itself. This study aims to determine the philosophy of Islamic education and the basic foundations of Islamic educational institutions. The research method uses qualitative with a literature study approach, emphasizing secondary sources obtained from books, journals and official reports. The study results explain that education requires a strong foundation or foundation for the majority of Muslims through Islamic educational institutions. It needs to be thoughtfully developed based on Islamic religious knowledge from the Al-Qur'an and hadith; then, Islamic scientific progress will progress. Building a philosophical orientation of Islamic education must pay attention to the concept of the growth of knowledge strongly driven by the Al-Qur'an and hadith as inspiration in achieving competitive Islamic educational institutions. Efforts to instil educational philosophy in Islamic educational institutions are required to guide and investigate knowledge from its source sincerely. The framework in Islamic educational institutions must contain the principles of ontology, epistemology, and axiology. The research implies civilization's progress in achieving Islamic education with an inseparable educational philosophy value. Keywords: Educational Philosophy, Basic Foundation, Islamic Educational